The Role of Gastronomy Tourism as a Local Community Enablers in Kampung Cikarag, Garut Regency - Firdaus Aulia Rahman; Sri Wahyuni; Syifa Ainurrohmah (Gastronomy Tourism Journal, 2023)
A massive of global trends that affect many sectors including food trends has threatened traditional food existence. In order to inherit a spirit of local wisdom preservation among the young generation, the writers initiated a social experiment at Kampung Cikarag in creating a holistic tourist attraction highlighting the local food and its immersive innovation to urban society. This gastronomy tourism development is carried out in Cikarag Village, Garut Regency in collaboration with the business manager of Villa Sarema and some members of a cooperative. The research method uses descriptive research methods with a qualitative approach. The analysis used is divided into two parts, there are internal factor analysis and external factor analysis which is then assisted by instruments in the form of a SWOT matrix (Strength, Weakness, Opportunity, Threats) and QSPM (Qualitative Planning Srategic Matrix). This program resulted in a recommendation for a gastronomic tourism program, that is "Hayu Mulih ka Desa" as an effort to reintroduce Indonesian food through a trip to Garut.